Pelatihan Fotografi Berbasis Multimodality Untuk Meningkatkan Nilai Ekonomis Pada Hasil Karya Peserta Didik Berkebutuhan Khusus (PDBK) - Fajar Ekawati, Febriani; Drajati, Nur Arifah; Sugini; Lailatun Nurul Aniq (PELITA NUSA TENGGARA, 2024)
Abstract This service is motivated by the results of the researchers' need analysis that Students with Special Needs at Special Schools only learn a few basic things such as sewing, gardening, making key chains where every graduate from Special Schools is expected to be able to work after completing their education. However, there has been no training or provision of techniques and strategies in photography as a means for selling Students with Special Needs’ products via websites or social media. The aim of this community service is to train Special Schools teachers to develop their competence in multimodality-based photography, which is expected to be applied in the classroom to increase the economic value of Students with Special Needs' work. The method used in this activity was training which was carried out in three stages, i.e., the preparation stage, implementation stage and reflection stage. The core training activities were held on July 8, 2024 offline at the Petit Boutique Hotel and online via Zoom Meeting. This training was attended by various teachers and principals of Special Schools from primary to secondary levels in Central Java. The result of this service was that teachers were able to teach their students effective ways to sell and promote photography results with modern technology that helps the sales process, using this technology effectively, making the photography training process easier. The implication of this service is as a reference for educational practitioners to improve the photography skills of SLB students in promoting their products. Abstrak Pengabdian ini dilatarbelakangi oleh hasil need analysis penulis bahwa Peserta Didik Berkebutuhan Khusus (PDBK) di Sekolah Luar Biasa (SLB) hanya belajar beberapa hal dasar seperti menjahit, berkebun, membuat gantungan kunci dimana setiap lulusan PDBK dari SLB diharapkan dapat berkarya setelah menyelesaikan pendidikan. Bagaimanapun, belum ada pelatihan maupun pemberian teknik dan strategi dalam fotografi sebagai sarana untuk penjualan produk PDBK melalui website maupun media sosial. Tujuan dari pengabdian masyarakat ini adalah untuk melatih guru SLB dalam mengembangkan kompetensinya dalam fotografi berbasis multimodality, yang diharapkan dapat diterapkan di kelas untuk meningkatkan nilai ekonomi karya PDBK. Metode yang digunakan dalam kegiatan ini yaitu pelatihan yang dilaksanakan melalui tiga tahapan yaitu tahap persiapan, tahap pelaksanaan, dan tahap refleksi. Kegiatan inti pelatihan dilaksanakan pada tanggal 8 Juli 2024 secara luring di Petit Boutique Hotel serta daring melalui Zoom Meeting. Pelatihan ini dihadiri berbagai guru dan kepala Sekolah Luar Biasa (SLB) dari jenjang dasar hingga menengah di Jawa Tengah. Hasil pengabdian ini adalah guru mampu mengajarkan kepada peserta didiknya cara efektif untuk menjual dan mempromosikan hasil fotografi dengan teknologi modern yang membantu proses penjualan, penggunaan teknologi tersebut dengan efektif sehingga mempermudah proses pelatihan fotografi. Implikasi pengabdian ini adalah sebagai acuan oleh praktisi pendidikan untuk meningkatkan ketrampilan fotografi peserta didik SLB dalam mempromosikan produk mereka.